Genome-wide identification and expression analysis of AUX/LAX family genes in Chinese hickory (Carya cathayensis Sarg.) Under various abiotic stresses and grafting - Yang, Ying; Wang, Jiayan; Xu, Yan; Abbas, Farhat; Xu, Dongbin; Tao, Shenchen; Xie, Xiaoting; Song, Feng; Huang, Qiaoyu; Sharma, Anket; Zheng, Luqing; Yan, Daoliang; et al. (Frontiers in Plant Science, 2023)
Auxin is essential for regulating plant growth and development, as well as plant response to abiotic stresses. The auxin influx transporter AUX/LAX protein belongs to the amino acid permease family of proton-driven transporters and is involved in the transport of indole-3-acetic acid (IAA). For the first time, eight cDNAs encoding the open reading frame of the Chinese hickory AUX/LAX family were identified and characterized. The family proteins were highly conserved. Evolutionary analysis showed that CcAUX/LAXs were more closely related to their homologous proteins in woody plants. Tissue-specific expression analysis of the CcAUX/LAX genes revealed that expression of this family members was higher in the root and lower in the stem. The promoters of CcAUX/LAX genes contained a large number of light responsive, hormone responsive, and abiotic stress responsive cis-regulatory elements. CcAUX/LAX genes responded differently to different levels of drought and salt stress treatments. Furthermore, expression analysis revealed that CcAUX/LAX genes played complex regulatory roles during Chinese hickory grafting. These findings will not only be regarded as a valuable resource for further functional validation of CcAUX/LAXs, but also contribute to a better understanding of the molecular basis for stress regulation by auxin in Chinese hickory.